Open space as an influential factor in housing prices in Klang valley, Malaysia - Asmawi, M. Zainora; Hj. Mohd. Noor, Norzailawati; Abdul Aziz, Abdul Razak (IIUM Press, 2017)
This book addresses the issue of how the provision of open space can be considered as an influential element in the house price. Literatures globally suggest that there is a significant value of open space in relation to house price in which the elements reflect more on the management parts such as the aspect of cleanliness and good maintenance of the open space. Apart from that, in term of the planning aspect, strategic location is essential in planning for open space. This research is a perceptual study reflecting the thoughts and opinions of the 200 respondents who were the house owners in four selected neighbourhoods, namely Taman Melawati, Bandar Baru Bangi, Subang Jaya and Shah Alam. The key question pertaining to the survey is whether the relationship between open place and house price exists locally and its character of the pattern and the intensity. Thus, the aim of this work is to study and examine the relationship between open space and house price in the selected four areas in terms of its pattern and strength. In order to obtain reliable data, this study applied mixed methods by using literature reviews, structured close-ended questions in questionnaire survey, an analysis of a GIS technique and site observation. The analysis covers the areas of the house price (transacted and offered price) in relation to the present housing market in those areas, compared with the views of the house owners, and how they perceived the importance of open space in house price. The findings indicate that the management aspects (cleanliness and maintenance) are the key micro factors perceived by the house owners when they decided to purchase their property. This demonstrates a positive correlation between open space and house price, reflecting the findings of the literatures. However, the regression analysis results show the strength is in moderation (R2 between 0.15 and 0.28). Consequently, the rate of house price change is rather small, which is slightly different from the secondary data of house price in those areas. In overall, this study has achieved its aims and also provided responses to the questions and finally achieved its objective of the inquiry.